Istoriografiya rekordnykh dostizhenii v skorostnom bege na kon'kakh - Volkov, N. I. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Through quantative analysis of the world records was conducted in the research. Author uses mathematical metods (graphics of curves, exponential curves and so on) to proof his hipothesis. Former lies on the following: a changing of the relative pace of record achievements depends of methodical breackthrough. By the author's opinion, training methods in skating roundly changed twice in XX century and the next methodical breaktrough will come at the beginning of third millennium.